2013
DOI: 10.5505/tjod.2013.43660
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Outcomes of Adolescent Pregnancy

Abstract: preterm do¤um (% 37.5, % 21.6), preeklampsi (% 31.3, % 14.7), intrauterin geliflme gerili¤i (% 20, % 9.8), fetal distres (% 20, % 8.8), konjenital anomali (% 16.3, % 5.9

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 10 publications
(14 reference statements)
1
11
0
2
Order By: Relevance
“…As reported by the authors, they were statistically significantly higher relative to the adult group [19]. …”
Section: Discussionmentioning
confidence: 55%
“…As reported by the authors, they were statistically significantly higher relative to the adult group [19]. …”
Section: Discussionmentioning
confidence: 55%
“…The fact that our results are higher than TNSA data can point out existence of unregistered adolescent marriages. In study of Melekoğlu and others (2013) it is confirmed that 52,5% of adolescent women do not have an legal marriage (Melekoğlu et al, 2013). That is known education status is related with adolescent marriages(Beattie et al, 2015; Kim, Longhofer, Boyle, & Brehm, 2013).…”
Section: Discussionmentioning
confidence: 68%
“…As a result of our study, we found increased maternal anemia, congenital fetal anomaly, preterm birth, preeclampsia, low birth weight and cesarean rates in adolescents. The incidence of adolescent pregnancies in the world varies between 1% and 42% depending on the level of development and cultural differences [12]. In a study conducted by Ayyıldız et al in Zonguldak, the incidence of adolescent pregnancy was found to be 3.7%, and it was found as to be 3.6% in Diyarbakır in a study conducted by Ağaçayak et al [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al reported a higher risk of central nervous system anomalies (anencephaly, spina bifida/meningocele, hydrocephalus/microcephaly) gastrointestinal system anomalies (omphalocele, gastroschisis) and musculoskeletal system anomalies (cleft lip/polydactyl, syndactyly) when they examine 5542861 nullipar pregnant women under 35 age [18]. Melekoğlu et al reported that 16.3% of infants born from adolescent pregnancies and 5.9% of infants born from non-adolescents had a congenital anomaly and the incidence was significantly higher in the first group [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation